Notched strength of fabric composite plates with a circular hole - Govindan Potti P.K.; Nageswara Rao B.; Srivastava V.K. (My University, 2025)
A modified point stress criterion is proposed for predicting the notched strength of composite plates having a circular hole. The analytical results are compared well with the existing test results of several woven fabric composite plates.